Pengaruh Tepung Daun Katuk, Tepung Kunyit dan Kombinasi Keduanya terhadap Ukuran Linear Tubuh dan Prediksi Bobot Badan Ternak Babi - Sea, Maria Margareta; Aryanta, I Made S.; Dodu, Tagu (Animal Agricultura, 2024)
This study aims to determine the effect of a combination of katuk meal (Sauropus androgynus L. Merr) and turmeric flour (Curcuma domestica) on linear body size and prediction of body weight of starter pig. The material usedwas 12 pigs castrated male landrace breeds aged 1-2 months. With an initial body weight range of 10.25 kg with a coefficient of variance (CV: 19.61%) The design used in this study was a randomized block design (RBD) with 4 treatments and 3 replications. The treatment tried was RO: 100% basal diets, R1: 100% basal diets + 4% katuk leaf meal , R2: 100% basal diets + 1% turmeric meal, R3: 100% basal diets + 4% katuk leaf meal and 1% turmeric meal. The variables measured in this study were chest circumference, body length, height and prediction of body weight. It was concluded that the use of the combination Frog leaf flour (Sauropus androgynus L.Merr) and turmeric flour (Curcuma domestica) at a level of 5% Combination of 4% TDKa and 1% Tku) have the same effect on chest circumference, body length, height and prediction of slag body weight of landrace starter phase pigs